2020
DOI: 10.1186/s12885-020-06792-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of Fibroblast growth factor receptor 1 (FGFR1) gene amplification and protein overexpression in hypopharyngeal and laryngeal squamous cell carcinoma

Abstract: Background: The gene encoding fibroblast growth factor receptor 1 (FGFR1) is emerging as a therapeutic and prognostic biomarker in various cancer types, including head and neck squamous cell carcinoma (SCC). Here, we investigated the clinicopathologic implication of FGFR1 gene amplification and protein overexpression in hypopharyngeal and laryngeal SCC.Methods: Fluorescence in situ hybridization and immunohistochemistry were performed to determine FGFR1 gene amplification and protein overexpression in 209 surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Hase et al , Young et al and Koole et al reported that FGFR1 was associated with poor outcome of HNSCC [ 17 , 31 33 ]. Kim et al recently found that FGFR1 amplification may serve as an independent prognostic factor for DFS in hypopharyngeal and laryngeal squamous cell carcinoma [ 34 ]. Our results are consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Hase et al , Young et al and Koole et al reported that FGFR1 was associated with poor outcome of HNSCC [ 17 , 31 33 ]. Kim et al recently found that FGFR1 amplification may serve as an independent prognostic factor for DFS in hypopharyngeal and laryngeal squamous cell carcinoma [ 34 ]. Our results are consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the upregulation of FGFR1 has been found in breast cancer, ovarian cancer and tongue squamous cell carcinoma ( 28 30 ). Similarly, the amplification of FGFR1 may serve as an independent prognostic factor for disease-free survival in LHSCC ( 31 ). Related studies have shown that HCG18 promoted the progression of lung adenocarcinoma by regulating miR-34a-5p-mediated hyaluronan mediated motility receptor expression ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies demonstrated that FGFR1 overexpression is related to poor prognosis in HPV-negative HNSCC patients, 31,33,34 whereas others suggest the contrary. 26,29,35 The perceived discrepancy may be attributed to a number of factors, including the difference in the cutoff value for FGFR1 expression, various anatomic positions of HNSCC, different sample size, and distinct patient ethnicities from different studies. In line with this suggestion, Fisher and colleagues 32 reported that the sensitivity of AZD4547, a selective FGFR inhibitor, is not associated with FGFR expression level in a panel of 10 HNSCC cell lines they examined, including both HPV-positive and HPV-negative cells.…”
Section: Fgfr1 Amplification and Overexpressionmentioning
confidence: 99%
“…However, at present, conflicting results in terms of FGFR1 expression as a prognosis biomarker have been reported. Multiple studies demonstrated that FGFR1 overexpression is related to poor prognosis in HPV-negative HNSCC patients, 31,33,34 whereas others suggest the contrary 26,29,35 . The perceived discrepancy may be attributed to a number of factors, including the difference in the cutoff value for FGFR1 expression, various anatomic positions of HNSCC, different sample size, and distinct patient ethnicities from different studies.…”
Section: Fgfr Genomic Alterations In Hnsccmentioning
confidence: 99%